2020
DOI: 10.1021/acs.jpclett.9b03447
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Control of Ultrafast Internal Conversion Using Nanoconfined Virtual Photons

Abstract: The rational control of nonradiative relaxation remains an unfulfilled goal of synthetic chemistry. In this study, we show how strongly coupling an ensemble of molecules to the virtual photons of an electromagnetic cavity provides a rational handle over ultrafast, nonradiative dynamics. Specifically, we control the concentration of zinc tetraphenyl porphyrin molecules within nanoscale Fabry−Perot cavity structures to show a variable collective vacuum Rabi splitting between cavity polaritons coincides with syst… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 39 publications
2
38
0
Order By: Relevance
“…47,77 This paradoxical behaviour has been reported in multiple systems but never explained. [51][52][53]75,76 We note that the transient transmission and reflectance data contain spectral signatures arising from the same parent states (based on spectral position) and exhibit a similar combination of dynamics spanning the sub-ps to 100-ps scale (Figure 2d). We thus consider them to report on the same physics and henceforth consider only the transmission data.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…47,77 This paradoxical behaviour has been reported in multiple systems but never explained. [51][52][53]75,76 We note that the transient transmission and reflectance data contain spectral signatures arising from the same parent states (based on spectral position) and exhibit a similar combination of dynamics spanning the sub-ps to 100-ps scale (Figure 2d). We thus consider them to report on the same physics and henceforth consider only the transmission data.…”
Section: Resultsmentioning
confidence: 91%
“…Accordingly, several subsequent studies using low-Q metallic cavities have reported intriguingly long polariton lifetimes (>1 ps) and alterations to intrinsic photochemical processes from energy transport to singlet fission. 33,36,[51][52][53][54][55][56] Crucially, the understanding of the dynamics in these experiments depends sensitively on the ability to robustly assign the observed spectral features to specific electronic states. In the studies on low-Q cavities, almost the entirety of the photoexcited response was assigned to photoexcited polaritons, with no direct signatures of the dark states reported.…”
Section: Introductionmentioning
confidence: 99%
“…48 On the contrary, Zn(II) porphyrins have relatively slow and inefficient internal conversion [48][49][50][51][52][53] in addition to a large S 0 / S 2 transition dipole moment. 54,55 As a result, producing a high-energy S 2 state of ZnTPP through TTA that is capable of transferring an electron to a nearby acceptor has been the subject of several recent reports. 53,56,57 Quenching of the Excited States in ZnTPP Once the feasibility of electron transfer from the S 2 state of ZnTPP was verified, quenching of the ZnTPP excited states (S 1 , T 1 , and S 2 ) was investigated through a combination of fluorescence (S 1 and S 2 ) and transient absorption (T 1 ) studies in the presence of acrylates.…”
Section: Feasibility Of Excited-state Electron Transfermentioning
confidence: 99%
“…13 These phenomena have been primarily investigated by forming molecular polaritons through coupling organic molecules with optical cavities. [12][13][14] However, funda-mental limitations of using organic molecules for generating polaritons are their short lifetime of electronic excitations and their relatively small transition dipoles that limits the magnitude of light-matter interactions.…”
Section: Introductionmentioning
confidence: 99%